Mediterranean land use systems from prehistory to antiquity: a case study from Peloponnese (Greece). Issue 1 (2nd January 2019) - Weiberg, Erika; Hughes, Ryan E.; Finné, Martin; Bonnier, Anton; Kaplan, Jed O.
ABSTRACT: Understanding the sustainability of land use systems over time requires an accounting of the diversity of land uses and their varying influences on the environment. Here we present a standardized review of land use systems in the Peloponnese, Greece, from the Neolithic to the Roman period ( 6500 BC–AD 300). Using a combination of sources, we synthesize the fundamental information required to characterize and quantify the spatial requirements of land use. We contextualize our results in a discussion of temporal trends, the probable drivers of change, and how these changes can be integrated with the general knowledge of these societies and the overall effect of land use across time. While our review concentrates on the Peloponnese, our methodology is widely applicable where suitable archaeological and historical records are available, and is broadly representative of the prehistoric and early historical evolution of agricultural land use systems in the eastern Mediterranean.